2011
DOI: 10.1016/j.ejcnurse.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Staff Views about Discussing Sexual Issues with Coronary Heart Disease Patients: A National Survey in Ireland

Abstract: Background: While a healthy sexual life is regarded as an important aspect of quality of life, sexual counselling from healthcare providers for cardiac patients has received little attention in the literature. Aim: To document current practice and assess the needs of cardiac rehabilitation service providers in Ireland with regard to sexual assessment and management for patients. Methods: Cardiac rehabilitation staff in all relevant centres in Ireland responded to a postal questionnaire. Sexual health managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 31 publications
6
65
0
2
Order By: Relevance
“…10 Furthermore, a US study on nurses working with patients after a myocardial infarction and national surveys in Ireland and Sweden in cardiac rehabilitation centers and coronary care unit teams have shown comparable findings. 11,14,16 It can be concluded that not discussing sexual health and providing sexual counseling in different cardiac settings is a general problem that does not only relates to HF nurses, but also other cardiac healthcare providers. This limited implementation of sexual counseling in practice may rightfully be called a concern, because a considerable number of HF patients experience sexual difficulties which have a negative effect on their own quality of life and that of their partners.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Furthermore, a US study on nurses working with patients after a myocardial infarction and national surveys in Ireland and Sweden in cardiac rehabilitation centers and coronary care unit teams have shown comparable findings. 11,14,16 It can be concluded that not discussing sexual health and providing sexual counseling in different cardiac settings is a general problem that does not only relates to HF nurses, but also other cardiac healthcare providers. This limited implementation of sexual counseling in practice may rightfully be called a concern, because a considerable number of HF patients experience sexual difficulties which have a negative effect on their own quality of life and that of their partners.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] To improve patient care in this area, it is important to learn which barriers prevent nurses from discussing sexual health 5 with their patients. A study among cardiac rehabilitation staff showed that barriers experienced included lack of training, the feeling that the patient is not yet ready to discuss issues related to sexual health, and a general lack of knowledge of sexual health.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations